Effect of Lifting Lug Hole Diameter Size on Strength Performance in Ship Block Lifting Process: English - Arifuddin, Andi Mursid Nugraha; Nizam, Syahrul; Pawara, Muhammad Uswah; Sitorus, Chris Jeremy Verian; Rachmianty, Andi; Ningrat, Andi; Baso, Suandar (Indonesian Journal of Maritime Technology, 2025)
The safety of the ship block lifting process is always a serious concern during the assembly of ship blocks. The block/structure and equipment must not be damaged during the lifting process. This study aims to determine the structural response values that occur with various hole diameter sizes of the lifting lug during the ship block lifting process. The object of this research is a ship block from the new construction of the Ferry Ro-Ro 1500 GT. The method used is numerical simulation based on finite element method (FEM) software. The simulation is conducted to obtain the stress and deformation values for each size of the lifting lug. The selected ship block load is the largest ship block load, which is 52,380 tons. The number of lifting lugs used in the simulation is 5, with varying diameters of 53, 58, 63, 68, and 73 cm. Based on the simulation results, the diameter of 63 mm gets the minimum normal and shear stress figures. While the minimum von misses stress figure is shown by the variation of the diameter of 73 mm. While the smallest deformation figure is shown by the variation of the diameter of 53 mm. In general, all variations of lifting lug holes can still be applied with the note that the weight of the load must be considered.